Relationship between the novel and traditional anthropometric indices and subclinical atherosclerosis evaluated by carotid intima-media thickness (c-IMT) - Costo-Muriel, Clara; Calderón-García, Julián F.; Rico-Martín, Sergio; Galán-González, Javier; Escudero-Sánchez, Guillermo; Sánchez-Bacaicoa, Carmen; Rodríguez-Velasco, Francisco J.; Santano-Mogena, Esperanza; Fonseca, César; Muñoz-Torrero, Juan F. Sánchez (Frontiers in Nutrition, 2023)
recent years, new anthropometric indices have emerged as an alternative to traditional indices to improve the prediction of fat percentage and its association with cardiovascular risk. The aim of this study was to evaluate the association of carotid intima-media thickness (cIMT) estimated by Doppler ultrasound with current anthropometric indices (traditional and novel). This was a cross-sectional study with a total of 789 Spanish patients. Traditional (BMI, WHR and WHtR) and novel (ABSI, AVI, BAI, BRI, CI, CUN-BAE and WWI) anthropometric indices were calculated, and carotid Doppler ultrasound was performed to evaluate cIMT (≥0.90 mm). Most of the anthropometric indices analysed were significantly higher among patients with pathological cIMT, except for BMI, BAI and CUN-BAE. In multiple linear regression analysis, cIMT was positively related to ABSI, AVI, BRI, CI and WWI but not to CUN-BAE, BAI or traditional anthropometric indices. Similarly, in univariate analysis, all indices were associated with a cIMT ≥ 0.90 mm (p<0.05), except BMI, BAI and CUN-BAE; however, only ABSI (aOR: 1.61; 95% CI: 1.08-2.40; p=0.017), CI (aOR: 1.73; 95% CI: 1.15-2.60; p=0.008), and WWI (aOR: 1.74; 95% CI: 1.14-2.64; p=0.009) were significantly associated in multivariate analysis. Finally, CI, ABSI and WWI provided the largest AUC, and BMI and CUN-BAE showed the lowest AUC. In conclusion, ABSI, CI and WWI were positively associated with pathological cIMT (≥ 0.90 mm), independent of other confounders.